Evaluation of a Community-Based Self-Management Program to Increase Access to Rehabilitation for People Living with HIV. (21st October 2019) - Solomon, Patricia; Salbach, Nancy Margaret; O'Brien, Kelly Kathleen; Nixon, Stephanie; Baxter, Larry; Gervais, Nicole
We qualitatively evaluated a novel educational program to help people living with HIV understand the role of rehabilitation, facilitate access to rehabilitation, and promote self-management of chronic disease in Canada. The program incorporated components of self-efficacy, client-centered care, peer education, and problem-based learning. Delivery of the community-engaged program was viewed as feasible and acceptable; however, a flexible delivery model was deemed important. Perceived learning was related to rehabilitation, advocacy, and taking responsibility for one's health. A co-leader model and access to online resources were strengths. Future work should assess the ability to apply advocacy knowledge and skills to access rehabilitation services.